32.4k views
4 votes
Simplify the expression.

1
5z + +9y+ +6z-6y
20
4
20
1
5z + +9y+ +6z-6y=
20
(Use the, operation symbols in the math palette as needed. Simplify ya
expression.)
4
20

Simplify the expression. 1 5z + +9y+ +6z-6y 20 4 20 1 5z + +9y+ +6z-6y= 20 (Use the-example-1
User Giltay
by
4.7k points

2 Answers

5 votes

Answer:

1

5z + 6z = 11z

2

9y + -6y = 3y

3

ANSWER ( 11z + 3y)

User Jayr
by
4.8k points
4 votes

Answer:

3.7 n^2 + 4n + 2.1

Explanation:

2.7 n^2 + n^2 = 3.7 n^2

6n - 2n = 4n

7.8 - 5.7 = 2.1

User Haych
by
5.4k points